A Project-Based Approach to Learning Form Finding of Structural Surfaces. Issue 3 (December 2015) - Adriaenssens, Sigrid; Pauletti, Ruy Marcelo Oliveira; Stockhusen, Knut; Gabriele, Stefano; Magrone, Paola; Varano, Valerio; Lochner-Aldinger, Irmgard
In the last two decades, a renewed interest has arisen, both from the structural engineering and architectural field, to exploit the elegance and structural efficiency of structural surfaces. This paper discusses a project-based course aimed at graduate architecture and civil engineering students to i) develop an in-depth understanding of the basics of surface structures, ii) cultivate relevant numerical and physical form finding proficiency, iii) communicate complex technical issues with peers and iv) problem scope, brainstorm and generate design alternatives for force-modeled systems. Because of the nature of the course and workshop objectives, the evaluation of the effectiveness is qualitative rather than quantitative. Therefore, the findings are supported by students' reactions captured in their course evaluations as well as their chosen careers paths after graduation. Since there is rarely room for the introduction of new courses in an established academic curricula, this paper also shows how the course can be adapted to project-based workshops which can vary in length from half of a day to three days. In conclusion, this paper is of interest to educators in structural engineering and architecture because it contributes to methods for effectively teaching structural surface structures.